Master and Disciple: Bertel Thorvaldsen’s Private Collection and Its Impact on Neoclassicism .......... 83 - Suba, Zoltán (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
At the birth of archeology as a new science, Neoclassicism appeared on the stage of decorative and visual arts as well as that of architecture. The fascination with the rediscovered artifacts of antiquity led artists not to just collect them, but also to utilize them to rethink the legacy of Classical art and create something new out of it. One of the most admired masters of Neoclassicism, the Danish sculptor Bertel Thorvaldsen, had his own collection of antiquities which is now preserved in the Thorvaldsen Museum in Copenhagen. In the following I will attempt to capture the impact that these artifacts and plaster casts had on his work, and also point out how important his role was in the education of apprentices during his Roman period. To demonstrate its significance, I will turn to his Hungarian apprentice, István Ferenczy, and drawings, statues, and letters to connect both the master and the disciple to the ancient past.